Diagnostic accuracy of different cut-off values of adenosine deaminase levels in tuberculous pleural effusion - Masood, Kiran Iqbal; Shahid, Shayan; Jabeen, Kauser; Farooqi, Joveria; Kerawala, Sabeika Raza; Irfan, Muhammad (Journal of the Pakistan Medical Association, 2022)
Objective: To assess the diagnostic accuracy of different cut-off values of pleural fluid adenosine deaminase levels as a diagnostic method for tuberculous pleural effusion. Method: The prospective study was conducted from 2014 to 2016 at the Aga Khan University Hospital, Karachi, and comprised pleural fluid samples of adult patients with and without tuberculosis which were tested for adenosine deaminase levels, and divided into tuberculosis group A and non-tuberculosis group B. Sensitivity, specificity, negative predictive value and positive predictive value were calculated using different cut-offs. Data was analysed using IBM SPSS (Statistical Package for Social Sciences) version 21.0 (IBM Corp., Armonk, NY). Results: Of 155 patients, 46(29.7%) had tuberculosis; 30(65.2%) males and 16(34.8%) females. Those who did not have tuberculosis were 109(70.3%); 69(63.3%) males and 40(36.7%) females. The adenosine deaminase levels were elevated in group A compared to group B (p<0.001). The cut-off of 30U/L showed the highest sensitivity (71.7%) and negative predictive value (87.4%), and a specificity of 82.6%. The cut-off of 50U/L showed the highest specificity (89.9%) with sensitivity 52.2%, and the cut-off of 40U/L showed the highest positive predictive value of 68.9% with sensitivity 67.4% and specificity 87.2%. Conclusion: Pleural fluid adenosine deaminase testing for diagnosing tuberculosis pleuritis revealed highest sensitivity and moderate specificity for cut-off value of 30U/L. Key Words: Tuberculosis, Pleural effusion, Adenosine deaminase, Diagnosis.